2014
DOI: 10.1016/j.biotechadv.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized tissue and cell-derived extracellular matrices as scaffolds for orthopaedic tissue engineering

Abstract: The reconstruction of musculoskeletal defects is a constant challenge for orthopaedic surgeons. Musculoskeletal injuries such as fractures, chondral lesions, infections and tumor debulking can often lead to large tissue voids requiring reconstruction with tissue grafts. Autografts are currently the gold standard in orthopaedic tissue reconstruction; however, there is a limit to the amount of tissue that can be harvested before compromising the donor site. Tissue engineering strategies using allogeneic or xenog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
290
0
8

Year Published

2016
2016
2107
2107

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(301 citation statements)
references
References 237 publications
(391 reference statements)
3
290
0
8
Order By: Relevance
“…Many authors report on the successful clinical use of decellularized bovine bone to reconstruct bone defects [25][26][27][28]. However, the number of articles dealing with the use of declerulated bovine bone grafts of large sizes is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors report on the successful clinical use of decellularized bovine bone to reconstruct bone defects [25][26][27][28]. However, the number of articles dealing with the use of declerulated bovine bone grafts of large sizes is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…These small pieces were then minced in distilled H 2 0 using a homogeniser (IKAT10, IKA ® Works Inc., NC, USA) to create an ECM slurry. The effect of decellularisation was evaluated, comparing native GP (no additional treatment prior to freeze-drying), to a detergent-based technique using 0.1 % sodium dodecyl sulphate (SDS; Sigma-Aldrich); following comparisons with other detergents commonly used for decellularisation (Cheng et al, 2014;Gilbert et al, 2006;Luo et al, 2016;Luo et al, 2015), results not shown. Decellularised GP slurry underwent two freeze-thaw cycles in a hypotonic buffer (10 mM Trizma hydrochloride and 5 mM ethylenediaminetetraacetic acid (EDTA) at pH 7.4), washed in saline (PBS), and treated for 1 h at room temperature in 0.1 % SDS.…”
Section: Decellularisation and Scaffold Fabricationmentioning
confidence: 99%
“…Continuous feedback mechanisms between the local cell population and ECM serve to maintain the structural and biochemical composition of the native tissue. 1,2 Alterations in the ECM structure, beyond a critical size, incurred by either traumatic injury or biochemical changes can introduce a cascade effect leading to the development of a disease state in the tissue. 2,3 This is especially prevalent in tissue such as articular cartilage, which is populated with a low density of semiquiescent chondrocytes known for poor regeneration of damaged tissue.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Alterations in the ECM structure, beyond a critical size, incurred by either traumatic injury or biochemical changes can introduce a cascade effect leading to the development of a disease state in the tissue. 2,3 This is especially prevalent in tissue such as articular cartilage, which is populated with a low density of semiquiescent chondrocytes known for poor regeneration of damaged tissue. 3 Weakening of the cartilage tissue structure can result in the formation of a local defect, which can act as the genesis point for progressive inflammation and wear, eventually leading to total degradation of the tissue and clinical osteoarthritis (OA), which currently affects over 27 million Americans.…”
Section: Introductionmentioning
confidence: 99%